Anti-EGFR therapeutic efficacy correlates directly with inhibition of STAT3 activity - Ung, Nelson (Landes Bioscience, 2014)
Several agents targeting the epidermal growth factor receptor (EGFR) have been FDA-approved to treat cancer patients with varying tumor types including metastatic colorectal cancer. Many patients treated with anti-EGFR therapy however do not respond and those that do initially respond often acquire resistance. Here we show a clear correlation between the efficacy of anti-EGFR inhibitors with their ability to inhibit STAT3 activity in A431 epidermoid carcinoma cells and in a series of wt K-RAS expressing human colon cancer cell lines. Furthermore, the ability of cetuximab to inhibit growth also correlated with its ability to inhibit STAT3 activity in tumor xenograft animal studies. In addition, stable knockdown of the STAT3 phosphatase, protein tyrosine phosphatase receptor delta (PTPRD) resulted in enhanced STAT3 activity and subsequent resistance to cetuximab in DIFI colon carcinoma cells. This resistance could be reversed by STAT3 inhibition. Finally, HN5 cells with acquired resistance to the EGFR tyrosine kinase inhibitor, AG1478 displayed greater STAT3 activity than the HN5 control cell line. These AG1478-refractory HN5 cells were re-sensitized to AG1478, cetuximab and erlotinib when co-treated with a STAT3 inhibitor. Taken together, our current data indicates a key role of STAT3 activity in promoting resistance to anti-EGFR therapy and suggests that anti-EGFR therapy in combination with inhibitors that block STAT3 may provide therapeutic benefit for patients with mCRC and other EGFR driven tumor types.